2002
DOI: 10.1038/419034a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of British hunting ban on fox numbers

Abstract: Pressure to ban the hunting of foxes with hounds in Britain has fuelled debate about its contribution to the control of fox populations. We took advantage of a nationwide one-year ban on fox-hunting during the outbreak of foot-and-mouth disease (FMD) in 2001 to examine this issue and found that the ban had no measurable impact on fox numbers in randomly selected areas. Our results argue against suggestions that fox populations would increase markedly in the event of a permanent ban on hunting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 2 publications
0
27
0
Order By: Relevance
“…Therefore, it is unlikely that fox populations in the three sites were limited by the level of culling. The impact of culling on fox populations is much debated, especially on large geographical scales (Hewson 1986;Baker et al 2004;Baker et al 2002;Aebischer et al 2003), and conclusions of those studies are contrasted. One of the key points explaining these contrasting results may be the various levels of culling effort applied in relation to fox densities.…”
Section: Reproductive Parametersmentioning
confidence: 97%
“…Therefore, it is unlikely that fox populations in the three sites were limited by the level of culling. The impact of culling on fox populations is much debated, especially on large geographical scales (Hewson 1986;Baker et al 2004;Baker et al 2002;Aebischer et al 2003), and conclusions of those studies are contrasted. One of the key points explaining these contrasting results may be the various levels of culling effort applied in relation to fox densities.…”
Section: Reproductive Parametersmentioning
confidence: 97%
“…In Eastern Hokkaido (Japan), hunting was increased in 1970 but despite that, the parasite is still present although at a low prevalence. A nation-wide hunting ban on foxes in the United Kingdom was reported not to have measurable impact on the fox population density in selected areas (Baker et al, 2002 cited by Kamiya et al, 2007). Kamiya et al (2007) concluded that fox hunting by culling or trapping does not have an effect on the number of foxes and therefore no effect on controlling EM.…”
Section: Tor2b)mentioning
confidence: 99%
“…1 The obvious point here is that 'country sports' is a broad church, and the chapter focuses upon recent social science empirical research on hunting. There is, of course, an important natural science literature in relation to foxes (see Harris 1993, Baker et al 2002 and game shooting (see GCT 2005), in addition to reflections by participants themselves (Sassoon 1999, Shilling 2004). However, the chapter seeks to challenge whether has a case that the academic community has evaluated the country sport of hunting via its own, dominant methodological paradigm and according to the agenda of the government, rather than seeking to explore the phenomena of hunting a priori.…”
Section: Research and The Hunting Issuementioning
confidence: 99%